(untitled) (Research, Society and Development, 2021)
Leadership is part of our daily lives, and emotional intelligence has been gaining prominence in studies. In this sense, this work aimed to understand the relationship of leadership and emotional intelligence in the formation of rural female leaders of the Marrecas Settlement, in São João do Piauí-PI. In order to achieve the objectives proposed in this work, a qualitative-descriptive research was carried out, data collection was carried out by means of a semi-structured interview, carried out with 5 (five) women who exercise leadership within the settlement. As a result, it was concluded that traits of transformational, situational (or contingency) and behavioral leadership; and aspects of emotional intelligence such as empathy, self-control, motivation and self-knowledge are at the heart of the interviewees’ female leadership training. Certainly, these characteristics are favorably promoting the construction and formation of the female leadership of this community, even in the face of their own insecurity, fear, difficulty in articulation and communication, in which, because they are women, they are still seen with “bad looks.” In addition to the difficulties in reconciling the functions, as a woman, of work and home and being judged for having to leave the house and go to work outside.